2017
DOI: 10.1007/s12035-017-0797-7
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Ameliorates Doxorubicin-Induced Cognitive Impairment (Chemobrain) in Experimental Rat Model: Impact on Oxidative, Inflammatory, and Apoptotic Machineries

Abstract: Chemobrain refers to a common sequelae experienced by 15-80% of cancer patients exposed to chemotherapeutics. The antineoplastic agent doxorubicin (DOX) has been implicated in a strenuous neurotoxicity manifested as decline in cognitive functions, most probably via cytokine-induced oxidative and nitrosative damage to brain tissues. Astaxanthin (AST), a naturally occurring carotenoid, is reputable for its outstanding antioxidant, anti-inflammatory, and antiapoptotic activities. Therefore, the aim of the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 75 publications
8
54
0
1
Order By: Relevance
“…Our findings of behavioral deficits with the Morris water maze align with previous studies examining rodent models of cognitive decline after mono-or poly-chemotherapy treatment; however, this is the first time it was shown using the AC-T regimen. Another study noted the protective capacity of antioxidants, using the antioxidant astaxanthin, which reversed doxorubicin-induced cognitive impairment in mice [27]. In our case, the addition of MnBuOE to AC-T treated mice maintained intact spatial memory retention.…”
Section: Discussionsupporting
confidence: 57%
“…Our findings of behavioral deficits with the Morris water maze align with previous studies examining rodent models of cognitive decline after mono-or poly-chemotherapy treatment; however, this is the first time it was shown using the AC-T regimen. Another study noted the protective capacity of antioxidants, using the antioxidant astaxanthin, which reversed doxorubicin-induced cognitive impairment in mice [27]. In our case, the addition of MnBuOE to AC-T treated mice maintained intact spatial memory retention.…”
Section: Discussionsupporting
confidence: 57%
“…Due to the extended π conjugation, astaxanthin reacts towards many free radical reductions, and the presence of polar ion rings containing hydroxylic and carbonyl groups provides it with higher antioxidative capacity compared to other carotenoids [174]. It has been demonstrated that treading rats with astaxanthin (25 mg kg −1 body weight) five times a week for four weeks, with simultaneous administration of high doses of doxorubicin (8 mg kg −1 body weight in total for 4 weeks), an anti-cancer agent with proven neurotoxic properties, resulted in improvement of cerebral oxidative stress parameters (Table 1), while behavioral tests demonstrated that the treatment significantly improved memory, restored the histopathological architecture of the hippocampus, limited oxidative and inflammatory damage, and reduced the increase in acetylcholinesterase activity [115]. An increase in GSH and SOD, and a decrease in MDA levels in the brains of rats poisoned with Cd was reported by Akkoyun et al [114].…”
Section: Vitamins and Provitaminsmentioning
confidence: 99%
“…AST treatment signi cantly protected against DOX-induced oxidative and in ammatory insults and downregulated the overactive apoptotic machineries [18]. Therefore, the current study extended such bene cial effects of EUG and AST by testing their combination with DOX in MCF7 to investigate, on mechanism-based, whether EUG and AST could enhance the sensitivity of HR+ MCF7 cells to DOX, and if so, whether these effects are linked to MDR-P-gp pathway and/or the non-MDR-epigenetic immunomodulation.…”
Section: Discussionmentioning
confidence: 99%